A Comprehensive Guide to Fully Inkjet‐Printed IGZO Transistors - Lorenzo Magnarin; Ben Breitung; Jasmin Aghassi‐Hagmann (Advanced Electronic Materials)
Abstract In this concise review, the recent advancements in fully inkjet‐printed (IJP) indium‐gallium‐zinc‐oxide (IGZO) thin‐film transistors (TFTs) over the past years are discussed. IGZO has replaced hydrogenated amorphous silicon (a‐Si:H) as the primary channel material for liquid‐crystal display TFTs and has gained further attention due to the solution processability of IGZO inks. Despite the longstanding practice of printing IGZO for approximately fifteen years, the realization of fully inkjet‐printed devices, including both dielectric and electrode components, represents a recent milestone in research, potentially heralding a cost‐effective era for IGZO transistors. In this review, following an introductory exposition of IGZO, the focus is on the different ink formulations, currently deployed for solution‐processed IGZO devices, the intricacies of the printing procedure involved are delineated, and ongoing research endeavors pertaining to the printing of dielectrics and electrodes for such devices are expounded upon.